Effects of different agro-ecosystems in the dynamic of nitrogen, phosphorous, and potassium in the tomato crop - Alberto Bouzo, Carlos; Domingo Astegiano, Eugenio (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this research was to evaluate the dynamics of nitrogen, phosphorous, and potassium in tomato crops and in different soils of agro-ecosystems. The research consisted of studying the effect of three agro-ecosystems: 1) agricultural (T1), natural (T2) and horticultural (T3). These agro-ecosystems are characterized by the sequence of the maize and wheat crops during 8 years (T1), natural vegetation of grasses (T2), and rotation of horticultural crops during 20 years (T3). The study was done in Santa Fe, Argentina (31° 15 ́ S, 60° 50' W) between 2009 and 2010, having used a hybrid tomato crop, round with indeterminate growth. The concentration of N-NO3- in the soils had a high value (> 65 ppm) at the beginning of the crop in the three agro-ecosystems. The concentration of P was also very high (> 250 ppm) in the horticultural agro-ecosystem (T3) and less than the rest, with approximately 50 ppm for T1 and 150 ppm for T2. The same occurred in this agro-ecosystem with K. The natural agro-ecosystem (T2) was the one that had the lowest concentration of P in the soil. The concentrations of N, P, and K resulted with highly significant differences (p≤ 0.01) in the concentrations of the stalks of the plants coming from the three agro-ecosystems. However, the concentrations of N and K were deficient towards the end of the study in the agricultural (T1) and natural (T2) agro- ecosystems.
Keywords: Solanum lycopersicum L.; nutrient concentrations; mineral nutrition; agricultural rotation